THE INFLUENCE OF FACTORS ON THE COSTS OF DIFFERENT TYPES OF LOANS IN BUSINESS OF AGRICULTURAL FARMS AND MEDIUM-SIZED AGRICULTURAL ENTERPRISES - Lutovac, Jelena; Djokić, Aleksandar; Borojević, Nebojša (Economics of Agriculture, 2024)
The application of the use of different types of loans in the real organization of agricultural production in Republic of Serbia was the focus of the authors of the study. The goal of the research was to determine the existence of legality based on the analysis of 7 factors affecting the loans of agricultural farms and medium-sized agricultural enterprises, namely: limit, repayment delay, efficiency, average exchange rate, possibility of repayment, increase in production, currency, as well as the overall score of all analyzed factors as well as the total score. Using the t test (Table 1), the authors found that there are significant differences in the evaluation of all 7 analyzed factors (p<0.0005*). In addition, the authors determined that there are significant differences in the evaluation of the use of three types of loans (p<0.0005*) by agricultural farms and medium-sized agricultural enterprises in the Republic of Serbia.